Konsep Keadilan menurut Aristoteles, Ibnu Khaldun, dan Korelasi dengan Undang-Undang 1945 Berdasarkan Implementasinya di Pemerintah Kelurahan Karangbesuki Malang - Muhammad Azrul Amirullah; Nabil Hafidz Alkhairi (Lembaga Yasin AlSys, 2025)
Philosophical and practical understanding of justice plays a crucial role in local governance systems, as reflected in Karangbesuki Subdistrict, Malang City. Justice, as a fundamental principle for establishing a harmonious, prosperous, and civilized society, has been discussed by Aristotle, who viewed it as granting each individual their due proportionately, and by Ibn Khaldun, who emphasized its role as the foundation for the continuity of civilization and societal welfare. This study aims to examine the concept of justice according to Aristotle and Ibn Khaldun and to analyze its correlation with the 1945 Constitution in village-level governance practices. A qualitative descriptive method was applied through literature review and in-depth interviews with subdistrict officials and local residents. The results reveal that justice-related values such as equality, honesty, courage, and responsibility have been pursued in public services, although participation and transparency remain challenges. The correlation between the philosophers’ ideas and Indonesia’s constitutional values is evident in the spirit of public service that upholds equal rights, law enforcement, and social protection. The study concludes that strengthening the understanding of justice through philosophical and religious approaches can reinforce the implementation of fair governance oriented toward public welfare.